PERBEDAAN TINGKAT KEPUASAN KERJA PERAWAT BERDASARKAN UNIT KERJA: LITERATURE REVIEW - Ida Ayu Putri Saraswati; Ni Putu Emy Darma Yanti; Kadek Eka Swedarma (Coping: Community of Publishing in Nursing, 2021)
Job satisfaction could affect various aspects in nursing practice such as productivity, performance, patient safety, nursing outcomes and service quality. The work environment can influence the level of nurses’ job satisfaction so those nurses working in different work units may have different levels of job satisfaction. This is a..literature review which aims to determine different levels of nurses' job satisfaction in different work units. The literatur searching was carried out through Google Scholar, Proquest, PubMed and ScienceDirect databases with specific keywords. Ten articles were selected based on inclusion and exclusion criteria. The results show that there are differences in the level of job satisfaction among nurses working in outpatient, inpatient, intensive care and emergency units. Job satisfaction of nurses working in diverse work units can be influenced by different variables. Work unit characteristics, including unit type, adequacy of the number of nurses, nurse to patient ratio, number of patients, complexity of patient care, job stress, work schedule, relations with other health workers are factors that influence differences in job satisfaction for nurses in each unit. Hospital management needs to make an effective strategic plan as an effort to improve nurse job satisfaction. Improving the quality of the work environment and work arrangements are needed to reduce nurses' work stress and increase nurse job satisfaction so as to produce quality health services.